A quantum chemical study of the interaction of carboxylic acids with DMSO - Ren, Mu; Rigele, Ao; Shun, Na; Natsagdorj, Narantsogt (Mongolian Journal of Chemistry, 2022)
Quantum chemical computational methods, which use quantum mechanics and molecular dynamics theory, have developed rapidly in the past few decades, and quantum chemical computation has penetrated almost all fields of chemistry. Hydrogen bonds are ubiquitously common weak intermolecular interactions. Moreover, the bonding mechanism of hydrogen bonds is considered to be different from that of chemical bonding. Because of the difficulty of experimental studies, a more accurate calculation of hydrogen bonding from theory is a more convenient and direct method to understand hydrogen bonding. Density functional theory (DFT) is the most widely used general function in quantum chemical calculations, giving accurate results for most chemical systems. In this paper, the geometries of the hydrogen-bonded dimer complex of acetic acid and DMSO was structurally optimized and potential energy surface was determined. The geometries of four related hydrogen-bonded dimer complexes were fully optimized using the M06-2X/6-311++G (3d, 2p) exchange-correlation functional with DFT-D3(BJ) empirical dispersion correction. We found that hydrogen bonding is a mixture of electrostatic interactions and covalent bonding, and that hydrogen bonding is a kind of force with different percentages of electrostatic and covalent character, rather than a special force independent of chemical bonding. Thus, more clearly defining our inherent classification of forces between substances provides a new perspective for our future study of weak interactions such as hydrogen bonding.